Social Entrepreneurship, Career Choice and Religiosity: Ziswaf Institution Perspective - Yudhi Anggoro; Tasnim Nikmatullah Realita; Roni Angger Aditama (Jurnal Ilmiah Ekonomi Islam, 2021)
Social entrepreneurship or social entrepreneurship has become an increasingly prominent topic. The development of social-based and oriented business units shows an increasing trend in line with the increasing public awareness of social problems that occur. Philanthropic institutions as a form of Social Entrepreneurship have taken on many social roles since several years ago. However, there are not many research results that examine it from a human resource perspective. Is it possible that being amil is a career choice? Is a question that has not been answered through scientific studies. This paper will examine these problems through a literature study that begins with a description of career theories and continues with a description of the research results that have been carried out. Special attention is paid to the relationship between career choice and religiousity because the ZISWAF institution is an institution based and driven by the principles of Islamic teachings.